Highlights of the updated Dutch evidence‐ and consensus‐based guideline on psoriasis 2017. (1st January 2019) - van der Kraaij, G.E.; Balak, D.M.W.; Busard, C.I.; van Cranenburgh, O.D.; Chung, Y.; Driessen, R.J.B.; de Groot, M.; de Jong, E.M.G.J.; Kemperman, P.M.J.H.; de Kort, W.J.A.; Karsch, S.A.; Lamberts, A.; et al.
Abstract: Linked Comment: Ormerod. Br J Dermatol 2019; 180 :11 .